Empowerment of Santriwan Through Scabies Transmission Prevention Training and Promotion of Clean and Healthy Living - Annisa; Feri Oswari; Fanie Indah Manik; Buhori; Dingin Sibayang; Novani Maryam Rambe; Fitria Ningsih; Imelda; Aryanes (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
The implementation of training programs aimed at students, instructors and the school community while at the Islamic boarding school is the main subject of this research. The program efficiently promotes healthy lifestyle choices such as quitting smoking, washing hands with soap, eating healthy snacks, exercising regularly, eliminating mosquito larvae, and disposing of trash properly. Through a variety of techniques, including discussion, debate, practical exercises, and assessments, the program effectively disseminates knowledge and ensures that it is put to use. Santriwan are considered agents of change who promote good behavior and advance public health. In summary, this study highlights the effectiveness of training programs in improving scabies prevention and highlights their potential to serve as a model for broader public health campaigns. More than just spreading knowledge, the project's primary goal is to promote behavior change by giving Santriwan the tools they need to make healthy lifestyle choices, have a positive impact on their environment, and improve the overall health of the community.